Anti-corruption compliance a guide for small and mid-sized organizations - Aiolfi, Gemma 1960- (Elgar compliance guides, 2020)
This indispensible book offers step-by-step guidance to small and mid-sized companies and non-profit organizations in managing corruption risks in overseas markets. It covers how and why to build a culture of integrity, develop a risk-based anti-corruption compliance programme, and engage with other industry players in collective action against shared corruption challenges. The focus on culture, compliance and collective action helps resource-stretched companies to build a strong foundation for a healthy and flourishing organization, as well as contribute towards raising standards of integrity across their industry. Key features include: Guidance for creating and contributing to collective action Quick definitions, tips and practical tools such as checklists A hands-on approach with an emphasis on culture and leadership Case studies and real-life examples of both corruption risks and the importance of a strong compliance culture. Anti-Corruption Compliance will be an invaluable resource for senior managers of small and mid-sized organizations in minimizing exposure to corruption risks in international markets. It will also prove useful to corporate lawyers and others involved with compliance functions in larger companies, as well as to academics and students of corporate law with an interest in anti-corruption and compliance"--